Challenges of Married Life for Couples Who Married at an Early Age Around the World, Seen from the Driving Factors and Solution Strategies - Elin Maulida Rahmawati; Mahmudah; Andi Kiswanto; Dewi Asiyah; Lela Nurlaila (Universitas PGRI Yogyakarta, 2026)
Early marriage is a common problem in low- and middle-income developing countries, bringing health, emotional, sexual, and social consequences. These challenges vary by country. This study aims to explore the challenges of early marriage, including its drivers and strategies for addressing them. This study employed a systematic literature review using the Scopus and Google Scholar databases, as they offer broad and credible academic coverage. Of the 151 articles identified, only 10 met the inclusion criteria, which included topic relevance, language, full-text accessibility, and a clear methodology. The results showed that couples who marry early are generally not physically and psychologically ready to assume the roles of husband and wife. Factors driving early marriage include residence, religion, limited access to education, poverty, family cultural structure, and low individual autonomy. One strategy for addressing this is through marriage counseling, which helps women plan pregnancies and prevent the negative impacts of early pregnancy. Keywords: early marriage, family, marriage counseling